Threads of blue - LaFleur, Suzanne M. (Wendy Lamb Books, 2017)
Mathilde escapes war-torn Sofarende and reunites with Megs and the other children who are working for the army to retake Sofarende from the enemy, but Mathilde must come to terms with her past treasonous actions and determine what she must do in order to prove her friendship to Megs.